1979
DOI: 10.1128/jcm.10.4.506-514.1979
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Clinical Isolates of Mycobacteria with Gas-Liquid Chromatography Alone

Abstract: Identification of 18 mycobacterial species was performed by analysis of profiles obtained by using gas-liquid chromatography. Organisms were saponified in methanolic NaOH, and the reaction mixture was treated with BF3 in methanol and extracted with a hexane-chloroform mixture. An identification scheme was developed from 128 stock strains and tested against a collection of 79 clinical isolates. By using gas-liquid chromatographic profiles alone, 58% of specimens were correctly identified to species level, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
1
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 27 publications
5
47
1
1
Order By: Relevance
“…Tisdall et al (28,29) demonstrated that fatty acid profiles obtained by gas-liquid chromatography (GLC) could in most cases identify to the level of species or "complex". In comparison with the identification obtained by biochemical profiles they demonstrated that the identity of 320 out of 335 clinical isolates agreed.…”
mentioning
confidence: 99%
“…Tisdall et al (28,29) demonstrated that fatty acid profiles obtained by gas-liquid chromatography (GLC) could in most cases identify to the level of species or "complex". In comparison with the identification obtained by biochemical profiles they demonstrated that the identity of 320 out of 335 clinical isolates agreed.…”
mentioning
confidence: 99%
“…The mycobacteria were saponified in NaOHcontaining (0.5 N) absolute methanol at 70 OC for 30 min, after which the free fatty acids were esterified with boron trifluoride-methanol and extracted with chloroform-hexane ( I :4 vol/vol). The extracts were then evaporated to dryness (9).…”
Section: Strains and Cultivationmentioning
confidence: 99%
“…The purpose of the present study was to compare chromatographic results from alkaline saponifica-tion of mycobacteria followed by methylation with results from direct acidic methanolysis. The test organisms were strains of the Mycobacterium avium-intracellulare complex and M. gastri, since these mycobacteria have been reported as difficult to distinguish by their GC fatty acid patterns (9,10).…”
mentioning
confidence: 99%
“…TBSA can be found in mycobacteriae o r nocardiae, but not in other bacteriae or in human tissue [9,10,11]. The detection of TBSA by gas chromatography/mass-spectrometry with selected ion monitoring (GC/MS-SIM) can be used for the diagnosis of pulmonary, as well as extrapulmonary tuberculosis [12][13][14][15][16][17][18][19][20][21][22][23]. This method provides a rapid, highly specific and sensitive diagnostic test for the presence of mycobacteria [20].…”
Section: Introductionmentioning
confidence: 99%